Insights into Wild‐Type and Mutant p53 Functions Provided by Genetically Engineered Mice. Issue 6 (5th February 2014) - Donehower, Lawrence A.; Soussi, Thierry
<x xml:space="preserve">Abstract</x> The TP53 tumor suppressor gene is the most frequently mutated gene in human cancers. Genetically engineered alterations of the Trp53 gene in the mouse germ line have been particularly useful in furthering our understanding of the functions of both the wildtype and mutant forms of p53 at the organismal level. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>